2017
DOI: 10.1177/1069397117736749
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Gratitude in Brazilian Children and Adolescents

Abstract: This study aimed to examine age-related changes in gratitude expression and spending preferences and the associations between children's greatest wish and gratitude expression. Participants were 285 children of ages 7 to 14 (M = 10.87, SD = 2.27, 54% girls) from public and private schools in Porto Alegre, a large urban center of Brazil. We found that verbal gratitude was the most common type of gratitude expression. Older children were more likely to express verbal and less likely to express concrete gratitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…For instance, expressing hedonistic wishes was linked to a lesser likelihood of expressing connective than verbal gratitude for Brazilians in comparison to Hispanics. This finding supports the view that hedonistic values hamper reciprocation involving perspective taking, at least for Brazilians (Freitas et al 2016;Liang and Kiang 2018;Mendonça et al 2018;Palhares et al 2018). This result may also suggest that, for Hispanics, there are other cultural values strengthening the expression of connective gratitude despite wishing for hedonistic things.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…For instance, expressing hedonistic wishes was linked to a lesser likelihood of expressing connective than verbal gratitude for Brazilians in comparison to Hispanics. This finding supports the view that hedonistic values hamper reciprocation involving perspective taking, at least for Brazilians (Freitas et al 2016;Liang and Kiang 2018;Mendonça et al 2018;Palhares et al 2018). This result may also suggest that, for Hispanics, there are other cultural values strengthening the expression of connective gratitude despite wishing for hedonistic things.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, Tudge et al (2015a) found a significant inverse association between connective gratitude and hedonistic wishes among children and adolescents in the United States. Moreover, other results indicated that concrete gratitude was positively associated with hedonistic wishes, and connective gratitude was positively associated with social-oriented wishes among Brazilian and Chinese children and adolescents (e.g., Freitas et al 2016;Liang and Kiang 2018;Mendonça et al 2018;Palhares et al 2018). Based on that, in the present study, we hypothesized that participants across ethnic groups who expressed hedonistic wishes would be more likely to express concrete than connective gratitude.…”
Section: Gratitude and Its Association To Wishesmentioning
confidence: 67%
See 2 more Smart Citations
“…Di dalam masyarakat Brazil, ungkapan syukur secara verbal adalah strategi yang paling umum dilakukan (Palhares, Freitas, Vargas & Tudge, 2018). Sedangkan pada masyarakat Cina dan Korea Selatan, ekspresi syukur connective yaitu membalas kebaikan benefactor dengan sesuatu yang diharapkan atau yang mungkin dibutuhkan oleh benefactor, menjadi strategi yang diutamakan (Mendonça, Mercon-Vargas dkk., 2018).…”
Section: Pendahuluanunclassified